Comparison of golf swing patterns in skilled female golfers among three different clubs - Nozawa, M.; Hashimoto, H.; Otsuka, M.; Yoshioka, S.; Isaka, T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to compare golf swing patterns using three different clubs among skilled golfers. Five right-handed female professional golfers used their own three clubs (driver, 5-iron, and 9-iron) to hit standard golf balls in our laboratory. 3D coordinates of body and club landmarks during the swing motions were recorded using a 3D motion capture system with operating at 250 Hz frame rates. As the results, the acceleration of club head in each club during downswing reached a maximum around about 0.08 s before impact during similar swing time, and the height of club head at the maximum acceleration showed about 55% of ratio for the body height despite differences of clubs. Skilled golfers therefore might feel as the similar patterns of golf swing even if they are swinging with different length clubs.